Bump in the wire (BITW) security solution for a marine ROV remote control application. (February 2018) - Rao, Muzaffar; Newe, Thomas; Omerdic, Edin; Kaknjo, Admir; Elgenaidi, Walid; Mathur, Avijit; Dooly, Gerard; Lewis, Elfed; Toal, Daniel
Abstract: The work presented here describes a Bump-In-The-Wire (BITW) security solution for the provision of secure communications for a Marine ROV Control Application. The targeted marine application involves controlling a 'Remotely Operated Vehicle (ROV)' from a remote control station through standard Internet. A BITW solution is required as communication through the Internet is inherently insecure and open to signal modification or tampering. BITW technology is an implementation approach that places a security mechanism outside and independent of the system that is to be protected, in this case that is a ROV and its remotely located control station. Secure communications between the ROV and the remote control station is necessary to ensure that only authorised persons can issue control commands to the ROV and that no unauthorised individual can understand/sniff the communications between the ROV and control station. The proposed BITW security solution involves an efficient implementation of the AES cryptographic algorithm on a Field Programmable Gate Array (FPGA) platform. The extra delay introduced into the remote control application was well within the allowable time window of 50 ms. Other security mechanisms can also be implemented in the same way depending upon the availability of hardware resources.